2008
DOI: 10.1007/s10725-008-9262-y
|View full text |Cite
|
Sign up to set email alerts
|

Does exogenous application of 24-epibrassinolide ameliorate salt induced growth inhibition in wheat (Triticum aestivum L.)?

Abstract: A greenhouse experiment was conducted to assess whether exogenously applied 24-epibrassionlide (24-epiBL) could alleviate the adverse effects of salt on wheat. Two hexaploid wheat (Triticum aestivum L.) cultivars, S-24 (salt tolerant) and MH-97 (moderately salt sensitive), were grown under control (0 mM NaCl in full strength Hoagland's nutrient solution) or saline conditions (150 mM of NaCl in full strength Hoagland's nutrient solution). After 41 days growth of wheat plants under saline conditions, 24-epiBL wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
79
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 168 publications
(104 citation statements)
references
References 53 publications
25
79
0
Order By: Relevance
“…A similar inferiority in the quantum yield of PS II was observed by Shahbaz et al (2008) in Triticum aestivum and by Hayat et al (2010) in Vigna radiata exposed to salinity.…”
Section: Discussionsupporting
confidence: 74%
“…A similar inferiority in the quantum yield of PS II was observed by Shahbaz et al (2008) in Triticum aestivum and by Hayat et al (2010) in Vigna radiata exposed to salinity.…”
Section: Discussionsupporting
confidence: 74%
“…This response may be associated to an effect of BRs on transcription and/or translation in the synthesis of pigments. Likewise, 24-EBR significantly enhanced the growth and photosynthetic capacity of salt-tolerant and salt-sensitive wheat plants [90]. As above, although exogenous BRs has been reported to improve the plant resistance to several abiotic stresses, there are controversies about the mode of action of endogenous BRs in plant stress responses.…”
Section: Effect Of Brs On Plant Growth Responses Under Drought and Samentioning
confidence: 82%
“…In parallel, EBR improved the antioxidant system, mitigating the accumulation of ROS, in addition to reducing the damage caused to the membranes and photosynthetic pigments. Plants treated with EBR presented greater accumulation of biomass as a result of the increased photosynthetic rates triggered by the efficient energy absorption and proper stomatal regulation (Arora et al 2008;Shahbaz et al 2008). Barbosa et al (2015) reported a reduction in the biomass of Saccharum spp.…”
Section: Discussionmentioning
confidence: 99%